ANALYSIS OF THE EFFECTIVENESS OF NATIONAL HEALTH INSURANCE (JKN) FINANCING ON THE QUALITY OF SERVICES IN FIRST-LEVEL HEALTH FACILITIES FROM THE PERSPECTIVE OF HEALTH LAW - Hempi Wanty Saragih; Marice Simarmata (Yayasan Multidimensi Kreatif, 2025)
The National Health Insurance (JKN) has been the main pillar in the implementation of the health system in Indonesia since its launch in 2014. With a financing scheme based on the principles of social solidarity and equity, JKN aims to improve the accessibility and quality of health services for the entire community. The First Level Health Facility (FKTP) as the front line of health services is expected to be able to provide quality services through a capitation financing mechanism. However, the effectiveness of this financing in improving the quality of services is still a debate in various circles, including in the aspect of health law that regulates the right to quality services. This study aims to analyze the effectiveness of JKN financing on the quality of services in FKTP with a health law approach as an analytical framework. This study uses a juridical-empirical method with data collection techniques in the form of surveys to patients, interviews with health workers, and analysis of related regulatory documents, such as Law Number 17 of 2023 concerning Health and Presidential Regulation Number 82 of 2018 concerning Health Insurance. Evaluation is carried out on the dimensions of service quality, including effectiveness, efficiency, accessibility, and patient safety, as well as conformity with health law principles such as fairness and non-discrimination. The results of the study show that the effectiveness of JKN financing in FKTP is still not optimal. The limited amount of capitation has an impact on low incentives for health workers and limited service facilities and infrastructure. As a result, some dimensions of service quality have not been fully met, such as long service waiting times and limitations in service types. From a health law perspective, this condition has the potential to violate patients' rights to quality and equal health services as mandated by law. These findings indicate the need to reformulate the JKN financing policy, especially in adjusting the capitation value based on service needs and workload in FKTP. In addition, strengthening regulations and supervision from related parties is very important to ensure that the principles of health law are implemented effectively. Thus, the quality of health services at FKTP can be improved in line with JKN's main goal in providing quality and fair health services for all levels of society. Based on the results of this study, it is suggested that the government conduct a thorough evaluation of the JKN financing scheme, strengthen supervision of FKTP, and integrate health law approaches in every health service policy. The application of the principles of health law will not only strengthen the rights of patients but also encourage the continuous improvement of the quality of services in first-tier health facilities.